2007
DOI: 10.1094/phyto-97-4-0470
|View full text |Cite
|
Sign up to set email alerts
|

New Populations of Sclerotinia sclerotiorum from Lettuce in California and Peas and Lentils in Washington

Abstract: Four populations of Sclerotinia sclerotiorum in North America were inferred previously, based on analyses of both rapidly evolving markers (DNA fingerprint and mycelial compatiblity), and multilocus DNA sequence spanning the range between fast and slow evolution. Each population was defined as an interbreeding unit of conspecific individuals sharing a common recent ancestor and arising in a unique evolutionary event. The present study applies this standard to extend characterization of S. sclerotiorum populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 55 publications
2
85
0
Order By: Relevance
“…MCGs identified Set 1 18 12 BR1; BR2, BR3, and BR5; BR4 and BR8; BR6; BR7; BR9; US1, US3, US4, and US7; US2; US5; US6; US8; and US9 Set 2 17 4 BR9 and BR23; BR10-BR21 and BR24; BR22; and US1 accumulate mutations and generate new genotypes, as reported elsewhere (Atallah et al, 2004;Kohli & Kohn, 1998;Malvárez et al, 2007;Wu & Subbarao, 2006). In experiment two, 81% of the isolates from Brazil belonged to a single MCG, even though these isolates were sampled over an extensive area with the furthest isolate separation of about 2,000 km.…”
Section: Isolates Mcgsmentioning
confidence: 68%
See 1 more Smart Citation
“…MCGs identified Set 1 18 12 BR1; BR2, BR3, and BR5; BR4 and BR8; BR6; BR7; BR9; US1, US3, US4, and US7; US2; US5; US6; US8; and US9 Set 2 17 4 BR9 and BR23; BR10-BR21 and BR24; BR22; and US1 accumulate mutations and generate new genotypes, as reported elsewhere (Atallah et al, 2004;Kohli & Kohn, 1998;Malvárez et al, 2007;Wu & Subbarao, 2006). In experiment two, 81% of the isolates from Brazil belonged to a single MCG, even though these isolates were sampled over an extensive area with the furthest isolate separation of about 2,000 km.…”
Section: Isolates Mcgsmentioning
confidence: 68%
“…The first report of S. sclerotiorum on soybean in the USA was from Illinois in 1946 (Chamberlain, 1951). Studies on DNA fingerprints and MCGs have shown that S. sclerotiorum populations show a higher diversity on a local scale, where boundaries have been established by genetic or phylogenetic means (Malvárez et al, 2007). Thus, the high diversity in the isolates found in that Brazilian field might indicate that population boundaries were present, favoring some level of outcrossing in addition to the probable intra-clonal variation, since each clone can Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Over a period of 20 years, population studies on S. sclerotiorum carried out in the Unites States and Canada have revealed a predominantly clonal mode of reproduction (Kohn et al, 1991;Kohli et al, 1995;Cubeta et al, 1997;Kohli and Kohn, 1998;Winton et al, 2006), with some evidence of outcrossing contributing to the population structure in a few temperate regions of North America (Atallah et al, 2004;Malvárez et al, 2007), as previously described in item 3.1.…”
Section: Sclerotinia Sclerotiorum Populations In North Americamentioning
confidence: 71%
“…MCGs or microsatellite markers have not been associated with specific virulence characteristics or ecological adaptations of the pathogen, and lack of variation in virulence among isolates from defined geographic areas has been reported in a number of studies on agricultural populations (Kohn et al, 1991;Kohli et al, 1992;Cubeta et al, 1997;Atallah et al, 2004;Auclair et al, 2004;Kull et al, 2004;Sexton and Howlett, 2004;Sun et al, 2005;Malvárez et al, 2007;Litholdo Júnior et al, 2011). Sexton and Howlett (2004) reported that among 44 isolates tested for virulence, the only two ones that caused relatively small leaf lesions were originally cultured from stem lesions rather than petals.…”
Section: Multiple Genetic Changes Associated With Gain Of Virulencementioning
confidence: 99%
“…Markers with high mutation rates such as microsatellites (also known as simple sequence repeats or SSRs) provide insights into recent divergence (Atallah et al 2010;Baumgartner et al 2010;Berbegal et al 2013;Dunn et al 2014;Dutech et al 2010;Goss et al 2009b), whereas mitochondrial, nuclear or other sequence loci provide inferences about the more distant evolutionary history given the slower mutation rates Goss et al 2009a;Malvarez et al 2007;Schoebel et al 2014;Stukenbrock et al 2007).…”
Section: Choosing and Using Molecular Markersmentioning
confidence: 99%